Real-time reverse transcription polymerase chain reaction development for rapid detection of Tomato brown rugose fruit virus and comparison with other techniques - Stefano Panno; Susana Ruiz-Ruiz; Andrea Giovanni Caruso; Ana Alfaro-Fernandez; Maria Isabel Font San Ambrosio; Salvatore Davino (PeerJ, 2019)
Background Tomato brown rugose fruit virus (ToBRFV) is a highly infectious tobamovirus that causes severe disease in tomato (Solanum lycopersicum L.) crops. In Italy, the first ToBRFV outbreak occurred in 2018 in several provinces of the Sicily region. ToBRFV outbreak represents a serious threat for tomato crops in Italy and the Mediterranean Basin. Methods Molecular and biological characterisation of the Sicilian ToBRFV ToB-SIC01/19 isolate was performed, and a sensitive and specific Real-time RT-PCR TaqMan minor groove binder probe method was developed to detect ToBRFV in infected plants and seeds. Moreover, four different sample preparation procedures (immunocapture, total RNA extraction, direct crude extract and leaf-disk crude extract) were evaluated. Results The Sicilian isolate ToB-SIC01/19 (6,391 nt) showed a strong sequence identity with the isolates TBRFV-P12-3H and TBRFV-P12-3G from Germany, Tom1-Jo from Jordan and TBRFV-IL from Israel. The ToB-SIC01/19 isolate was successfully transmitted by mechanical inoculations in S. lycopersicum L. and Capsicum annuum L., but no transmission occurred in S. melongena L. The developed real-time RT-PCR, based on the use of a primer set designed on conserved sequences in the open reading frames3, enabled a reliable quantitative detection. This method allowed clear discrimination of ToBRFV from other viruses belonging to the genus Tobamovirus, minimising false-negative results. Using immunocapture and total RNA extraction procedures, the real-time RT-PCR and end-point RT-PCR gave the same comparable results. Using direct crude extracts and leaf-disk crude extracts, the end-point RT-PCR was unable to provide a reliable result. This developed highly specific and sensitive real-time RT-PCR assay will be a particularly valuable tool for early ToBRFV diagnosis, optimising procedures in terms of costs and time.